PENGAWASAN PENDIDIKAN ISLAM DI MADRASAH TSANAWIYAH PERSIAPAN NEGERI 4 MEDAN - Rahmadi Ali (Jurnal Al-Fatih, 2018)
Supervision or often called supervision is a very important activity in the practice of education. Supervision activities are needed as control activities for all educational activities to direct, supervise, foster and control the achievement of all educational objectives, further this activity also has responsibility in improving the quality of education, both the process and the results, so that supervisory activities are carried out from the planning stage to the evaluation stage which will function as a feed back follow-up to improve and improve the quality of education towards better those who are classified as successful are those who always emphasize academic activities, always monitor and always supervise academic activities.